MEDIATION EFFORTS IN POLYANDRY CASES IN WEST KOTAWARINGIN REGENCY - Khudori, Sofyan; Khair, Abdul; Soeradji, Elvi; Fauzi, Fitriya (EMPOWERING HUMANITY, 2025)
Polyandry, although rare, is a complex and controversial phenomenon in Indonesia, including in West Kotawaringin District. These cases often involve conflicts of law, religious norms and customs that require specialized resolution approaches. This article aims to explore the effectiveness of mediation as a dispute resolution method in polyandry cases in the region. Using a descriptive qualitative approach, the research relies on in-depth interviews with perpetrators, mediators, religious leaders, customary leaders, as well as analysis of relevant legal documents. The results show that mediation has significant potential in resolving polyandry cases, especially as this approach prioritizes dialogue, mutual understanding and adjustment to local norms. However, the success of mediation is often constrained by differences in legal interpretation between adat and religion, lack of mediator capacity, and resistance from the parties involved. Nonetheless, some cases were successfully resolved through adaptive mediation, resulting in solutions that were more acceptable to all parties. The research concludes that mediation can be an effective alternative in resolving polyandry disputes if supported by trained mediators, collaboration between stakeholders, and a culture-based approach. Strategic recommendations include improving the training of local mediators and strengthening the integration between customary, religious and state laws to create sustainable solutions.